Interacting with chatbots later in life: A technology acceptance perspective in COVID-19 pandemic situation - Iancu, Ioana; Iancu, Bogdan (Frontiers in Psychology, 2023)
Within the technological development path, chatbots are considered an important tool for economic and social entities to become more efficient and to develop customer-centric experiences that mimic human behavior. Although artificial intelligence is increasingly used, there is a lack of empirical studies that aim to understand consumers’ experience with chatbots. Moreover, in a context characterized by constant population aging and an increased life-expectancy, the way aging adults perceive technology becomes of great interest. However, based on the digital divide (unequal access to technology, knowledge, and resources), and since young adults (aged between 18-34 years old) are considered to have greater affinity for technology, most of the research is dedicated to their perception. The present paper investigates the way chatbots are perceived by middle-aged and ageing adults in Romania. The age-range of the subjects is 40-78 years old, a convenience sampling technique being used (N=235). The timeframe of the study is May-June 2021. Thus, the COVID-19 pandemic is the core context of the research. . An online opinion survey has been conducted. The results show that while perceived ease of use is explained by the effort, the competence, and the perceive external control in interacting with chatbots, perceived usefulness is supported by the perceived ease of use and subjective norms. Furthermore, individuals are likely to further use chatbots (behavioral intention) if they consider this interaction useful and if the others’ opinion is in favor of using it. Gender and age seem to have no effect on behavioral intention.